Protective factors for psychological distress in hospital staff during the Coronavirus pandemic - Shirzad, Boshra; Kianimoghadam, Amir Sam; Tajik, Maryam; Bakhtiari, Maryam (Researcher Bulletin of Medical Sciences, 2024)
Background and Objective: The aim of the current study was to investigate three factors, including coping, resilience, and spiritual well-being as protective factors for the development of PD among hospital staff during the COVID-19 pandemic. Materials and Methods: In the current research, convenience sampling method was used to select 300 hospital staff from various hospitals in Tehran. The collected data were analyzed using multiple statistical methods, i.e., Pearson’s correlation coefficient, Structural Equation Modeling, and regression analysis. Results: The findings revealed that nearly 40 percent of the study sample experienced a severe mental disorder. Also, the study findings showed that there was a significant positive correlation between various aspects of spiritual well-being among hospital staff, i.e., communication with self and with God (P<0.01, r=0.676), communication with others and with God (P<0.01, r=0.605) and with self (P<0.01, r=0.626), and lastly communication with nature and with God (P<0.01, r=0.686) and with self (P<0.01, r=0.722) and with others (P<0.01, r=0.640). The results of the simultaneous regression analysis indicated that the three variables of coping, resilience, and spiritual well-being explained 0.072% of the total variance in psychological distress among the hospital staff sample. Conclusions: The findings of the current study suggested that the three factors of coping, resilience, and spiritual well-being may have a minimal protective role in PD development among the hospital staff population. More research is necessary to draw a conclusion on the role of these variables regarding PD